FAZLUR RAHMAN’S TAFSIR THOUGHTS ABOUT SATAN AND EVIL - Awwaliyah, Neny Muthiatul; Tajuddin, Tabrani (Sekolah Tinggi Agama Islam Sadra, 2024)
This article discusses the re-interpretation of the use of satan and evil in the Qur’an which needs to receive a response and be addressed or understood through a neo-modernist interpretation which is transcendental-metaphysical in nature. Satan is often associated with the cause of evil, especially when humans who commit crimes are thought to be influenced or inspired by Satan. The relationship between Satan and evil seems to be inherent and related. A re-interpretation of meaning is needed so that the meaning of Satan and evil can be aligned with other scientific terms empirically and strengthen intellectuals in positioning the Qur’an as a source of inspiration. Methodologically, Fazlur Rahman’s approach in analyzing the meaning of Satan and evil based on intellectual principles is to position the Qur’an as a holy book that is systematic, rational, experimental, and leads to scientific investigation. This pattern converges on the understanding of satan and evil in the Qur’an in two propositions. First, the use of satan and personal evil is influenced by the expressions of early Muslim society related to Makkiyah verses. Secondly, the meaning of satan is a fundamental principle in the life system of advanced civilized society which is related to the verses of nature and character. These two propositions provide the conclusion that satan and evil are one of the terms in the Qur’an which have various meanings that emphasize the aspects of function and guidance according to the context and form of use of the chosen words.